2021
DOI: 10.3390/ijms22094315
|View full text |Cite
|
Sign up to set email alerts
|

Barley Seeds miRNome Stability during Long-Term Storage and Aging

Abstract: Seed aging is a complex biological process that has been attracting scientists’ attention for many years. High-throughput small RNA sequencing was applied to examine microRNAs contribution in barley seeds senescence. Unique samples of seeds that, despite having the same genetic makeup, differed in viability after over 45 years of storage in a dry state were investigated. In total, 61 known and 81 novel miRNA were identified in dry seeds. The highest level of expression was found in four conserved miRNA familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 118 publications
3
12
0
Order By: Relevance
“…Barley is one of the cultivar species with long seed viability, however this depends on the humidity of the samples. Grains stored for 45 years in gene bank conditions present different levels of germination at about 86.7% and 2% [42]. Analysis of total RNA showed that both samples had degraded rRNA particles in comparison to the control, however miRNA and mRNA fractions were stable in all samples [43].…”
Section: Discussionmentioning
confidence: 95%
“…Barley is one of the cultivar species with long seed viability, however this depends on the humidity of the samples. Grains stored for 45 years in gene bank conditions present different levels of germination at about 86.7% and 2% [42]. Analysis of total RNA showed that both samples had degraded rRNA particles in comparison to the control, however miRNA and mRNA fractions were stable in all samples [43].…”
Section: Discussionmentioning
confidence: 95%
“…SPL genes can increase the expression of miR172, and miR156/SPLs/miR172 constitute the regulatory network of aging pathway ( Wei et al, 2017 ; Werner et al, 2021 ). Additionally, miR168 was involved in seed senescence in barley ( Puchta et al, 2021 ). In legumes, miR156 and miR172 were essential regulators of nodulation in soybean ( Yan et al, 2013 ; Yun et al, 2022 ), common bean ( Nova-Franco et al, 2015 ) and alfalfa ( Aung et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a huge need for new biochemical or molecular markers of seed viability that improve the process of monitoring plant material during storage in gene banks and to help with the understanding of the concomitant aging process occurring in seeds. These studies have developed rapidly over the last decade and substantiate the importance of volatile organic compounds [ 94 , 95 , 98 ], proteomic studies [ 191 ], RNA integrity [ 192 , 193 , 194 , 195 , 196 ] and DNA damage markers or epigenetic marks [ 96 , 97 , 99 , 190 , 197 , 198 , 199 , 200 ] that are highly promising and should be more widely explored.…”
Section: Discussionmentioning
confidence: 99%